Heat and Mass Transfer Pasta Semi-Infinite Vertical Porous Plate in MHD Flows in Turbulent Boundary Layer - Ngesa, Joel Ochola; Awuor, Kennedy Otieno; Abonyo, Jeconia Okello (World Journal of Research and Review (WJRR), 2018)
This study addresses the problem of unsteady free convection incompressible MHD fluid flow past a semi-infinite vertical porous plate in the presence of a strong magnetic field inclined at an angle  to the plate with Hall and Ion-Slip currents. It investigates the effects of Grashof number, heat source parameter, suction velocity, time, angle of inclination, Ion-Slip, Hall current and mass diffusion parameter on the convectively cooled or convectively heated plate restricted to turbulent boundary layer of the flow field. The partial differential equations governing the flow problem considered in our study are solved by a finite difference approximation while the computation of skin friction, rate of heat transfer and mass transfer at the plate is achieved by Newton’s interpolation approximation over the first five points.The results show that the Hall current, Schmidt number, Modified Grashof number, heat source parameter, suction velocity, time, angle of inclination, Ion-Slip currenton the convectively cooled or convectively heated plate affect the velocity, temperature and concentration profiles. Increases in Hall parameter cause a decrease in both primary and secondary profiles while increase in Ion Slip current parameter leads to increase in primary velocity profiles but a decrease in secondary velocity profiles. Consequently, their effects alter the skin friction, rate of mass transfer and the rate of heat transfer
Keywords: Heat transfer; Mass transfer; MHD; Turbulent flow; Semi-infinite plate; Hall and Ion-Slip currents